Eye exercises of acupoints: their impact on myopia and visual symptoms in Chinese rural children. Issue 1 (December 2016) - Lin, Zhong; Vasudevan, Balamurali; Fang, Su; Jhanji, Vishal; Mao, Guang; Han, Wei; Gao, Tie; Ciuffreda, Kenneth; Liang, Yuan
Abstract Background Chinese traditional "eye exercises of acupoints" have been advocated as a compulsory measure to reduce visual symptoms, as well as to retard the development of refractive error, among Chinese students for decades. The exercises are comprised of a 5-min, bilateral eye acupoint self-massage. This study evaluated the possible effect of these eye exercises among Chinese rural students. Methods Eight hundred thirty-six students (437 males, 52.3 %), aged 10.6 ± 2.5 (range 6–17) years from the Handan Offspring Myopia Study (HOMS) who completed the eye exercises and vision questionnaire, the convergence insufficiency symptom survey (CISS) questionnaire, and had a cycloplegic refraction were included in this study. Results 121 (14.5 %) students (64 males, 52.9 %) performed the eye exercises of acupoints in school. The multiple odds ratio (OR) and 95 % confidence interval (CI) for those having a "serious attitude" towards performing the eye exercises (0.12, 0.03–0.49) demonstrated a protective effect for myopia, after adjusting for the children's age, gender, average parental refractive error, and the time spent on near work and outdoor activity. The more frequently, and the more seriously, the students performed the eye exercises each week, the less likely was their chance of being myopic (OR, 95 % CI: 0.17, 0.03–0.99), after adjusting for the same confounders. However, neither the "seriousness of attitude" of performing the eye exercises (multipleβ coefficients: -1.58, p  = 0.23), nor other related aspects of these eye exercises, were found to be associated with the CISS score in this sample. Conclusions The traditional eye exercises of acupoints appeared to have a modest protective effect on myopia among these Chinese rural students aged 6–17 years. However, no association between the eye exercises and near vision symptoms was found.